Development of porous FeCo by liquid metal dealloying: Evolution of porous morphology and effect of interaction between ligaments and melt. (15th October 2019) - Joo, Soo-Hyun; Wada, Takeshi; Kato, Hidemi
Abstract: Liquid metal dealloying is a promising technique for synthesizing non-noble porous materials by preventing oxidation in a metallic melt. This method considers the heats of mixing between precursor elements and a melt element to design miscible and immiscible elements for a precursor. In this study, Ni and Co were selected as the miscible elements in an Mg melt as constituents of (FeCo)100− x Ni x precursor alloys to understand the complex mechanisms of their dissolution behavior. Dissolution of the second miscible element, Co, was governed by the composition of the Mg melt, because the characteristics of the melt changed in the presence of a high amount of dissolved Ni and its convection. The synthesized FeCo ligaments showed morphology variations depending on the dealloying temperature: the ligaments become more elongated along the dealloying direction at higher temperatures. A double-gyroid-like porous structure with a narrow liquid channel, produced from the (FeCo)70 Ni30 precursor, exhibited the highest specific surface area at all processing temperatures from 600 °C to 800 °C. This structure differed completely from that of the typical porous Fe80 Cr20 alloy produced under the same liquid metal dealloying conditions. Elongation resulted from time-dependent directional coarsening behavior that was affected by the composition of the Mg melt. Graphical abstract: Unlabelled Image Highlights: First demonstration of 3D interconnected porous FeCo materials produced by liquid metal dealloying Ligament morphology depends on ordering and coarsening mechanisms at different temperatures. Strong interaction between FeCo ligaments and the Mg melt affected coarsening behavior. Double-gyroid-like structure showed the highest specific surface area. Prerequisite conditions for dissolution of the second miscible element are identified.